2003
DOI: 10.1096/fj.02-0379fje
|View full text |Cite
|
Sign up to set email alerts
|

UV induces VEGF through a TNF‐α‐independent pathway

Abstract: Vascular endothelial growth factor (VEGF) is a potent keratinocyte-derived angiogenic factor. Prior reports suggest that following UV irradiation VEGF in keratinocytes is induced primarily by tumor necrosis factor (TNF)- alpha, a cytokine synthesized and secreted by keratinocytes after UV irradiation. We investigated whether blocking TNF-alpha binding to its receptors would inhibit UV-induced VEGF expression and secretion in the keratinocyte-derived line SCC-12F. Irradiation with physiologic UV doses (30 mJ/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 43 publications
1
17
0
4
Order By: Relevance
“…Low-dose Neisseria gonorrhoeae infection of a macrophage cell line induced IL-8 production without TNF␣ induction (47). Ultraviolet irradiation of a keratinocyte-derived cell line induces vascular endothelial growth factor production through a TNF␣-independent pathway (48). A thrombin study using human umbilical vein endothelial cells showed that IL-8 expression and E-selectin secretion were induced through a TNF␣-independent pathway (49).…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose Neisseria gonorrhoeae infection of a macrophage cell line induced IL-8 production without TNF␣ induction (47). Ultraviolet irradiation of a keratinocyte-derived cell line induces vascular endothelial growth factor production through a TNF␣-independent pathway (48). A thrombin study using human umbilical vein endothelial cells showed that IL-8 expression and E-selectin secretion were induced through a TNF␣-independent pathway (49).…”
Section: Discussionmentioning
confidence: 99%
“…80,81 Additionally, thrombospondin-1, an angiogenesis inhibitor, was down-regulated and platelet-derived endothelial cell growth factor, an angiogenesis activator, was up-regulated in keratinocytes exposed to UVB. 82 These changes in gene expression may contribute to the telangiectases seen in sun-exposed areas as well as facilitate the growth of UV-induced neoplasms.…”
Section: Vascular Alterationsmentioning
confidence: 99%
“…153 Certainly, this remains an area ripe for future investigation, as the complex interplay between matrix degeneration and vascular homeostasis in rosacea has yet to be clearly defined.…”
Section: Future Studiesmentioning
confidence: 99%